50.3k views
3 votes
Sum of the numbers m and n decreased by their product; write the algebraic expression​

2 Answers

4 votes

Final answer:

The algebraic expression for the sum of the numbers m and n decreased by their product is written as m + n - (m \times n).

Step-by-step explanation:

The student has asked for the algebraic expression for the sum of the numbers m and n decreased by their product. The algebraic expression that represents this is:

m + n - (m \times n)

This algebraic expression first adds the numbers m and n together, which is represented by m + n, and then subtracts their product, m \times n. The subtraction symbolizes the decrease by their product.

To write this expression, one must understand the rules of algebraic operations and the order of operations, where multiplication and division are carried out before addition and subtraction, unless grouped by parentheses.

User Chris Spicer
by
4.9k points
3 votes

Answer: m+n-mn

You can write mn as m*n

=================================

Step-by-step explanation:

The sum is the result of adding two or more numbers. Saying the sum of m and n means m+n.

Then we subtract off the product of m and n. The product is the result of multiplying m and n. We say m*n or mn to indicate their product.

Overall, we end up with m+n-mn

User Alcamtar
by
5.8k points